Eine hebräisch-ägyptische Parallele für die Frömmigkeit von Kindern - Bojowald, Stefan (Biblische Notizen, 2025)
The present article seeks to prove another Egyptian-Hebrew parallel. In the current case it is about the special relationship between gods and little children. In the literature of both people one example is referred to. The similarities between Egyptian literature and especially the Psalter, which have often been discussed, continue to increase.